A Bacterial Pathogen Senses Host Mannose to Coordinate Virulence - Wei, Lifan; Qiao, Haoxian; Sit, Brandon; Yin, Kaiyu; Yang, Guanhua; Ma, Ruiqing; Ma, Jiabao; Yang, Chun; Yao, Jun; Ma, Yue; Xiao, Jingfan; Liu, Xiaohong; et al. (iScience, 2019)
Bacterial pathogens are thought to activate expression of virulence genes upon detection of host-associated cues, but identification of the nature of such signals has proved difficult. We generated a genome-scale defined transposon mutant library in Edwardsiella piscicida, an important fish pathogen, to quantify the fitness of insertion mutants for intracellular growth in macrophages and in turbot (Scophthalmus maximus). These screens identified EvrA, a transcription activator that induces expression of esrB, a key virulence regulator. EvrA is directly bound and activated by mannose-6-phosphate (man-6P) derived from actively imported mannose. Mutants lacking EvrA or expressing an EvrA unable to bind man-6P were similarly attenuated in turbot. Exogenously added mannose promoted E. piscicida virulence, and high levels of mannose were detected in fish tissue. Together, these observations reveal that binding of a host-derived sugar to a transcription factor can facilitate pathogen sensing of the host environment and trigger virulence programs. [Display omitted] •An E. piscicida defined mutant library is generated and analyzed in vitro and in vivo•EvrA is a key transcriptional activator of the known virulence regulator esrB•EvrA is directly bound and activated by mannose-6-phosphate from imported mannose•Extracellular mannose augments E. piscicida virulence in an evrA-dependent manner Pathogenic Organism; Microbiology; Fish Culture